2015
DOI: 10.1016/j.cell.2015.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Silencing Mutants Reveals Complex Regulation of the Arabidopsis Methylome

Abstract: In our study, we surveyed the methylomes of 86 gene-silencing mutants by whole-genome bisulfite sequencing (BS-seq) and revealed interactions between DNA methylation pathways as well as new regulators of DNA methylation. One of the observations that we made was that mutation in histone deacetylase 6 (HDA6) resulted in loss of methylation at a small subset of sites in the genome. It has recently come to our attention that our hda6 mutant line was contaminated and thus our hda6 mutant data set did not represent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
272
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(301 citation statements)
references
References 1 publication
28
272
1
Order By: Relevance
“…It seems likely that this is due to the substantial overlap between CHH E class loci with D and E type loci in CG and CHG contexts that we have previously demonstrated. 46 We hypothesize that loss of methylation in the CHG and CG contexts caused by disruption to the RNA-independent maintenance pathways has a knock-on effect on CHH methylation for these loci, consistent with the findings of Stroud et al 54 Class A & B loci, which represent direct and indirect methylation by the mobile signal behave identically for the examined mutants in the Stroud et al set. For CHG context methylation, Figure 2.…”
Section: Classes Of Interaction and Mechanisms Of Methylationsupporting
confidence: 79%
See 1 more Smart Citation
“…It seems likely that this is due to the substantial overlap between CHH E class loci with D and E type loci in CG and CHG contexts that we have previously demonstrated. 46 We hypothesize that loss of methylation in the CHG and CG contexts caused by disruption to the RNA-independent maintenance pathways has a knock-on effect on CHH methylation for these loci, consistent with the findings of Stroud et al 54 Class A & B loci, which represent direct and indirect methylation by the mobile signal behave identically for the examined mutants in the Stroud et al set. For CHG context methylation, Figure 2.…”
Section: Classes Of Interaction and Mechanisms Of Methylationsupporting
confidence: 79%
“…To investigate further the mechanisms by which the classes of sRNA-methylation interaction are differentiated we compare the methylation profiles of the class A & B loci in 86 mutants of RNA silencing components using the data of Stroud et al 54 to those observed at the E & F class loci and relate these profiles to the model 19 of RdDM initiation, establishment, RNA-dependent maintenance and RNA-independent maintenance, and to the DDM1 chromatin remodelling pathway. 25 Examining the behavior of the identified loci in the Stroud et al knockout mutant dataset (Fig.…”
Section: Classes Of Interaction and Mechanisms Of Methylationmentioning
confidence: 99%
“…Functional redundancies among the different DCL proteins have been reported or suggested in many studies [27][28][29][30]. Despite the role of DCL3 in generating 24-nt siRNAs, the dcl3 mutant does not exhibit a severe decrease in DNA methylation levels at RdDM loci [31]. It has been thought that other DCL proteins could also process RDR products, compensating for DCL3 when it is absent, and that the 21/22-nt siRNAs, though less efficient, could also be fed into Argonaute (AGO) proteins [20].…”
Section: Introductionmentioning
confidence: 99%
“…Transcribed protein-coding genes are associated with permissive chromatin marks. In contrast, transcriptionally repressed genes and repetitive elements are typically labeled by histone H3 Lysine 27 trimethylation (H3K27me3), histone H3 Lysine 9 dimethylation (H3K9me2), and/or high-density DNA methylation in all cytosine sequence contexts in plants Stroud et al, 2013). While H3K27me3 ensures tissue-specific developmental transcription (Lafos et al, 2011), the role of H3K9me2 and promoter DNA methylation is to minimize the activities of repetitive elements, which frequently include retrotransposons (Mosher et al, 2009;Slotkin et al, 2009;Ibarra et al, 2012).…”
Section: Introductionmentioning
confidence: 99%